2001
DOI: 10.3354/ame026181
|View full text |Cite
|
Sign up to set email alerts
|

Use of NOx- microsensors to estimate the activity of sediment nitrification and NOx- consumption along an estuarine salinity, nitrate, and light gradient

Abstract: Microprofiles of nitrate plus nitrite (NO x -) were measured in sediment cores sampled at 6 stations along a nitrate and salinity gradient and a depth transect in Randers Fjord, Denmark. Rates of NO x -production and consumption were calculated from the concentration profiles to describe the variation of these processes under in situ conditions. A microscale biosensor for NO x -was used to obtain NO x -profiles in darkness and under in situ light conditions. This new tool for nitrate plus nitrite measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…As a result, denitrification was restricted to a sediment layer that was about 3 mm thick. The presence of such thin zones of denitrification has been reported previously for stream sediments (6), lake sediments (14,15,19), and estuarine sediments (4,20).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…As a result, denitrification was restricted to a sediment layer that was about 3 mm thick. The presence of such thin zones of denitrification has been reported previously for stream sediments (6), lake sediments (14,15,19), and estuarine sediments (4,20).…”
Section: Resultsmentioning
confidence: 82%
“…The integrated N 2 O production rates determined in the acetylene block core incubations, the direct nitrate flux determinations, and the reactive transport modeling results all point to the high capacity for nitrate removal by the intertidal estuarine sediments in the upper Scheldt Estuary (21). High rates of benthic denitrification supported by nitrate uptake from the water column, similar to those at Appels (37 to 60 nmol N cm Ϫ2 h Ϫ1 ), have been reported for nitrate-rich streams (ϳ120 nmol N cm Ϫ2 h Ϫ1 ) (7) and eutrophic estuaries in Denmark (40 to 140 nmol N cm Ϫ2 h Ϫ1 ) (4,20). The experimentally calibrated reactive transport model provides further insight into the role of the kinetic parameters and the overlying water chemistry in denitrification activity in the sediments (Table 2).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The bulk nitrification rates estimated in this study are at the lower end of those normally observed in Danish shallow estuaries and coastal waters (Binnerup et al 1992, Jensen et al 1996, Hansen & Kristensen 1998, but within the range of 0 to 1.8 mmol m -2 d -1 measured by NO 3 -/NO 2 -sensors in another Danish fjord (Meyer et al 2001). Only a few studies have measured nitrification rates in association with burrow structures (see Mayer et al 1995 for review), and of these the majority report potential rates (slurry assays at high NH 4 + concentrations) as opposed to measured rates.…”
Section: Discussionmentioning
confidence: 85%
“…The NO 2 Ϫ sensor was constructed like the NO x Ϫ biosensor except that the culture of bacteria used (Stenotrophomonas nitritireducens) was deficient in NO 3 Ϫ reductase (22). Concentrations of NO x Ϫ , NO 2 Ϫ , and O 2 in porewater were measured as three or more replicate profiles from at least two different cores, as described by Meyer et al (20). Profiles of NO 3 Ϫ were calculated by subtracting the averaged NO 2 Ϫ profile from the averaged NO x Ϫ profile.…”
Section: Methodsmentioning
confidence: 99%